Studies on Histology, Histochemistry and Micrometry of Hippocampus of Goat (Capra hircus) - Rawat, Pushpendra; Dubal, Subhash C.; Gori, Harishbhai P.; Pathak, Prashant K. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The brain of six adult goats was collected for the study of hippocampus. Harris’ Haematoxylin and Eosin (H&E) staining method was used for general microscopic structure of the hippocampus. Aldehyde-Thionin-PAS method was utilized for Nissl’s substance and mucopolysaccharides. Vogt’s method was used for nerve cells, Sevier-Munger method for neural tissues and the micrometry of hippocampus was performed for various layers of cornu ammonis and dentate gyrus. The mean values of thickness of different layers of cornu ammonis were measured by micrometry. Microscopic study revealed that the hippocampus was consisting of six layers, viz., alveus, stratum oriens, stratum pyramidale, stratum radiatum, stratum lacunosum and stratum moleculare. The hippocampus commissure and the dentate gyrus showed PAS positive reaction. Furthermore, these structures also showed a positive reaction with silver nitrate staining (Sevier-Munger staining). The study revealed that almost all the fibres of hippocampus were myelinated.
Keywords: Goat; Hippocampus; Histochemistry; Histology; Micrometry